Effects of aliskiren on blood pressure and humoral factors in hypertensive hemodialysis patients previously on angiotensin II receptor antagonists. (November 2014) - Ito, Takayasu; Ishikawa, Eiji; Fujimoto, Naoki; Okubo, Setsuya; Ito, Goro; Ichikawa, Takehiko; Nomura, Shinsuke; Ito, Masaaki
Abstract Background: A direct renin inhibitor (DRI), aliskiren, may be effective for blood pressure (BP) control in hemodialysis patients. However, it is unclear whether aliskiren has a greater beneficial effect on BP and humoral factors than angiotensin II receptor antagonists (ARBs) in hypertensive patients on hemodialysis. Methods: Eighteen hemodialysis patients (58 ± 14 years) on the recommended dose of an ARB were prospectively randomized into two groups: ARB and DRI groups. Patients in the ARB group continued taking their previous ARB, whereas those in the DRI group switched to aliskiren (150 mg/day) for 12 weeks. Baseline measurements of BP and humoral factors such as plasma renin activity (PRA), plasma aldosterone concentration (PAC) and brain natriuretic peptide (BNP) were performed. Measurements were repeated every 4 weeks. Results: At baseline, no differences were observed in age, gender or BP between the two groups. Systolic BP was unaffected by treatment in either groups (group effect, p = 0.26; time effect, p = 0.38; group × time effect, p = 0.24). PRA decreased in DRI (p ≦ 0.02, group effect, p = 0.65; time effect, p = 0.13; group × time effect, p = 0.048), but not in ARB (p ≧ 0.94). PAC increased only in DRI (p ≦ 0.03), whereas BNP was unaffected in either group. Conclusion: Aliskiren at a dose of 150 mg/day had a similar effect on BP compared with ARBs, but significantly lowered PRA.